Contextual Teaching and Learning Interactive Media in Redox Reaction Concept for Improving Critical Thinking and Self-efficacy - Abdul Hamid; Gita Maharani; Muhammad Kusasi; Rusmansyah Rusmansyah; Tien Tien Lee (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
Many students find redox reactions challenging due to educators focusing solely on imparting knowledge without real-world connections. This approach limits critical thinking and reduces students' self-efficacy. To address these issues, fostering creativity and developing interactive learning materials are essential solutions. This research aims to create contextual teaching and learning (CTL) based interactive learning media for redox reactions. This media focuses on validity, practicality, and effectiveness in enhancing students' critical thinking skills and self-efficacy. The research framework employed in this study follows a research and development method with an analysis, design, development, implementation, and evaluation (ADDIE) model, with a research subject of 31 students. The results showed that interactive learning media was declared valid by media experts and material experts with an average score of 92.50% (high validity category). Media is very practical based on readability tests, students' responses, teachers' responses and observation sheets average percentage of 85.92%. It is also proven to increase critical thinking skills in high effective category (N-gain 0.81), and increase self-efficacy in moderate category (N-gain 0.65).